Self-assessment and woman’s health control location after gynaecological operations - Rogala, Angelina; Janiszewska, Mariola; Dziedzic, Małgorzata; Żołnierczuk-Kieliszek, Dorota; Blicharski, Tomasz (Medical Studies/Studia Medyczne, 2016)
Introduction: Surgical treatment in gynaecology has a specific influence on a woman’s life and has a psychological effect because of the organs involved. Self-assessment and women’s health control location after gynaecological operation determine the treatment and rehabilitation process. Aim of the research : Self-assessment and women’s health control location after gynaecological operation evaluation was the aim of this study. Material and methods : There were 167 women after gynaecological treatment evaluated. Patients were registered in the Obstetrics and Gynaecology department and the Gynaecology outpatient Clinic in Chełm Public Specialist Hospital. MHCL version B scale with polish adaptation (Z. Juszyński) and sociodemographic, self-evaluation, and health control questionnaires created by the authors were used. This analysis used Kołmogorow-Smirnow, U Mann-Whitney and Kruskal-Wallis tests. Confidence intervals of p < 0.05 and p < 0.01 were established. IBM SPSS Statistics software was used. Results and conclusions : Most of the women after their gynaecological operations (61.1%) revealed their health perception as good and only one (0.6%) as poor. Over half of the patients self-assessed themselves as a valuable person (56.3%) and womanlike (55.1%), whilst a small number of patients stated as not attractive, impoverished, worse than others, useless, or worthless. The highest self-assessment scores were from women in early stages after their operation, e.g. from one month to one year after treatment (M = 14.95). MHLC scale analysis showed that most of the patients overbalanced internal health self-control (M = 25.33), indicating that life control is dependent on the patient. Respondents who stated their health status as poor in every health control scale had higher results. Age and education had a significant influence on the MHCL and self-assessment scales (p < 0.001).